Policy process diffusion: Transforming the governance model in Chinese cities - Bingqin Li; Lijie Fang (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper studies the increasing migrant population in Chinese cities that created serious challenges for the hosting cities. Ignoring migrants' need for a social integration population might help the government or host society save money in the short term, however, it can sow the seeds of social instability in the long term. Local governments in China are concerned that they have to cope with the economic, social and political pressure resulting from a rapid growth in the urban population. Following the abolishment of the Detention and Eviction System (Shourong Qiansong Zhidu) in 2005, the treatment of migrant workers and migrants in general improved significantly. Until 2015, migrant workers gained greater access to social insurance contributions and benefits, while rural−urban migrant children could attend urban schools. In some smaller cities and large cities in the west, migrant workers could access government-subsidized housing. However, these policy changes did not fully satisfy the demands of the migrant population. This may be due to policies being poorly designed or difficult to implement. It may also be a result of migrants' responses that stem, for example, from marginalization vis-à-vis the urbanization agenda or lack of trust in the system.
Keywords: 330